2011
DOI: 10.1182/blood-2010-05-283218
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial and distinct roles of α5 and α4 integrins in stress erythropoiesis in mice

Abstract: To delineate the role of specific members of ␤ 1 integrins in stress erythropoiesis in the adult, we compared the response to phenylhydrazine stress in 3 genetically deficient models. The survival of ␤ 1 -conditionally deficient mice after phenylhydrazine is severely compromised because of their inability to mount a successful life saving splenic erythroid response, a phenotype reproduced in ␤ 1 ⌬/⌬ reconstituted animals. The response of bone marrow to phenylhydrazineinduced stress was, unlike that of spleen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 55 publications
3
53
1
Order By: Relevance
“…Mice were injected subcutaneously with PHZ 24 (50 mg kg À 1 in sterile saline). After 7 days, they were killed and blood was collected from the caudal vena cava.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were injected subcutaneously with PHZ 24 (50 mg kg À 1 in sterile saline). After 7 days, they were killed and blood was collected from the caudal vena cava.…”
Section: Methodsmentioning
confidence: 99%
“…Acute anaemic stress triggers the rapid accumulation of new EC by a process distinct from steady-state erythropoiesis, and resembling the one of fetal definitive erythroid cells. Stress erythropoiesis was induced in vivo by injecting WT and Ulk1 gt/gt mice with the haemolytic agent phenylhydrazine (PHZ) 24 . These mice showed significant and comparable reductions in the number of circulating EC, compared with untreated mice (Supplementary Fig.…”
Section: Lc3-ii/lc3-i (Ratio) Rc Ec Eb Wt Dko Rc Ec Eb Rc Ec Eb Rc Ecmentioning
confidence: 99%
“…29 These mice do not mount a splenic erythroid response to hemolytic stress, but the mechanistic underpinnings of their poor stress Erythroid cells generated in the absence of specific β1-integrin heterodimers accumulate reactive oxygen species at homeostasis and are unable to mount effective antioxidant defenses We have previously reported that β1 D/D mice have a markedly impaired response to hemolytic stress, but the mechanisms of this were unclear. In the present study we explored in detail quantitative, phenotypic and functional aspects of erythropoiesis at homeostasis in a large number of animals for each of 3 murine models with specific β1 heterodimer integrin deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Expression of β1 parallels that of α4 with the exception that it is retained in terminally maturing cells. Pioneering work published, among others, by the Papayannopoulou laboratory has identified that the α4β1 heterodimer prevents mobilization of stem/progenitor cells in response to a variety of stimuli, including those that elicit the erythroid stress response.…”
mentioning
confidence: 99%